An Outbreak of Vancomycin-Resistant Enterococcus faecium in an Acute Care Pediatric Hospital: Lessons from Environmental Screening and a Case-Control Study - Steven J Drews; Susan E Richardson; Rick Wray; Renee Freeman; Carol Goldman; Laurie Streitenberger; Derek Stevens; Cristina Goia; Danuta Kovach; Jason Brophy; Anne G Matlow (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The present study describes a vancomycin-resistant enterococci (VRE) outbreak investigation and a case-control study to identify risk factors for VRE acquisition in a tertiary care pediatric hospital.